Conceptual Framework for Improving Supply Chain Cycle Times Through Distributed Fulfilment Models - Oladipupo Fasawe,; Oyenmwen Umoren,; Christiana Onyinyechi Makata, (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
The acceleration of global commerce and rising customer expectations have made supply chain cycle time reduction a critical strategic objective. This paper presents a conceptual framework for improving cycle times through distributed fulfillment models, which decentralize inventory and order processing across multiple nodes. The review synthesizes recent advances in supply chain network design, digital technologies, and logistics optimization, highlighting how distributed fulfillment leverages data-driven decision-making, automation, and last-mile innovations. Key considerations include balancing cost and responsiveness, managing demand variability, and aligning with sustainability goals. By integrating theoretical perspectives and empirical findings, the framework provides a foundation for rethinking traditional centralized fulfillment and positions distributed models as a transformative enabler for supply chain resilience and competitive advantage.
Keywords: Supply Chain Cycle Time; Distributed Fulfillment; Logistics Optimization; Supply Chain Resilience; Inventory Decentralization; Last-Mile Delivery